Principal Leadership Strategy in Managing the Dompu Integrated Islamic Vocational High School - Hermansyah, Hermansyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
In the journey of SMK IT Dompu, it cannot be separated from the role of a leader who is fully responsible for managing the SMK in expanding and developing the institution, to make students, educators and education personnel who have reliable skills and personalities. The leader has the task of directing and organizing educational institutions in order to achieve the desired goals. In carrying out their duties and functions, the Principal has their own leadership strategy which greatly influences the performance of the education personnel in their respective work environments. Failure and success are largely determined by the principal, because the principal is the controller and determiner of the direction the school wants to take towards its goals. The formulation of the problem in this study is as follows (1) What is the leadership strategy of the Principal of Integrated Islamic Vocational School Dompu in managing the Integrated Islamic Vocational School? (2) What are the leadership characteristics of the Principal of Integrated Islamic Vocational School Dompu in managing the Integrated Islamic Vocational School? (3) What are the efforts of the Principal in realizing the Integrated Islamic Vocational School Dompu? This study aims to describe (1) The leadership strategy of the vocational school principal in managing the Dompu Integrated Islamic Vocational School, (2) The leadership characteristics of the vocational school principal in managing the Dompu Integrated Islamic Vocational School, (3) The efforts of the vocational school principal in realizing the Dompu Integrated Islamic Vocational School. Penelitian ini menggunakan metode penelitian lapangan yaitu metode wawancara, observasi dan dokumentasi. Data yang terkumpul selanjutnya dianalisis dengan menggunakan metode analisis deskriptif interpretatif, dengan menggunakan pendekatan fenomenologi. Simpulan penelitian. Terdapat empat strategi pokok dalam mengelola yaitu: (1) perencanaan, (2) pengorganisasian, (3) melaksanakan pekerjaan sesuai dengan perencanaan yang telah ditetapkan, (4) melaksanakan tugas pengawasan dan pengendalian. Adapun ciri-ciri kepemimpinan kepala sekolah (1) menggunakan prinsip Rasulullah Muhammad SAW yaitu “Uswatun Khasanah” (teladan dalam bertutur kata, berbuat dan berperilaku), Upaya kepala SMK dalam mewujudkan SMK Islam Terpadu Dompu yaitu: (1) peningkatan mutu tenaga pendidik, (2) peningkatan mutu peserta didik, (3) perbaikan administrasi sekolah, (4) kegiatan belajar mengajar yang kondusif, (5) peningkatan sarana dan prasarana, (6) kurikulum yang bermutu dengan mengacu pada kurikulum 2013 (7) penerapan manajemen berbasis sekolah.